Talking about female genital mutilation : a guide to safeguarding for professionals who work with children - Lisa, Caroline (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This workbook is designed to be used to facilitate discussion and to disseminate awareness amongst all professionals (social workers, teachers and health care professionals) who are required by law to report instances of Female Genital Mutilation (FGM). Suitable for use in group settings, it requires no prior knowledge of the subject, but is written in such a way for anyone to be able to facilitate a session with colleagues, which takes between one-three hours depending on the facilitator and group's needs. Designed to be concise, it will give busy professionals a quick and effective tool to disseminate information to as many colleagues as possible to allow them develop understanding of a legal requirement of their job which has real and life-saving benefits for children"--
Keywords: Female circumcision; Clitoridectomy; EDUCATION / Educational Policy & Reform / School Safety & Violence; MEDICAL / Nursing / Maternity, Perinatal, Women's Health; SOCIAL SCIENCE / Customs & Traditions